2015
DOI: 10.1080/02640414.2015.1056821
|View full text |Cite
|
Sign up to set email alerts
|

Incremental training intensities increases loads on the lower back of elite female rowers

Abstract: Lumbar-pelvic kinematics change in response to increasing rowing stroke rates, but little is known about the effect of incremental stroke rates on changes in joint kinetics and their implications for injury. The purpose of this study was to quantify the effects of incremental rowing intensities on lower limb and lumbar-pelvic kinetics. Twelve female rowers performed an incremental test on a rowing ergometer. Kinematic data of rowers' ankle, knee, hip and lumbar-pelvic joints, as well as external forces at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…It is very likely that increased fatigability of lower limb muscles influenced spinal motion. Accordingly, Buckeridge et al 5 . found that shear and compressive forces on the L5/S1 segment increases at higher loads, while peak knee extensor moments decreased.…”
Section: Spatial Changes In the Distribution Of Lumbar Es Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…It is very likely that increased fatigability of lower limb muscles influenced spinal motion. Accordingly, Buckeridge et al 5 . found that shear and compressive forces on the L5/S1 segment increases at higher loads, while peak knee extensor moments decreased.…”
Section: Spatial Changes In the Distribution Of Lumbar Es Activitymentioning
confidence: 99%
“…Following the application of testing equipment (HDEMG electrodes, electrogoniometer and heart rate monitor; see below for details), the rowers performed a 5 16 .…”
Section: Testing Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Two specialist journals that exhibit such a positivist spirit are the Journal of Sports Economics and the Journal of Sports Sciences, in both of which the typical article sets out to analyse how sporting results can be optimised. Current topics range from difficulties in talent selection (Faber et al, 2016;Furley and Memmert, 2016) and biases in athlete remuneration (Deutscher and Büschemann, 2016) to measures for injury prevention (Buckeridge et al, 2016) and sources of success (Lago-Peñas and Sampaio, 2015;Pitts, 2016).…”
Section: Instrumentalist and Romantic Approaches To Statistics In Sportmentioning
confidence: 99%
“…Collaboration between Imperial College and British Rowing has used the ‘Flock of Birds’ (Ascension Technologies, USA) EM tracking system lower extremity and lumbar spine biomechanics research on elite rowers, offering a framework to describe proper sequencing (Bull et al 1998 ; Bull and McGregor 2000 ; McGregor et al 2004 ) and establishing links between biomechanics parameters and performance metrics, which continue to be used to analyze quality of elite rowing technique (Buckeridge et al 2016 , 2015 ; Murphy 2009 ). However, current generation EM systems still present drawbacks, which relate to the functional range of accuracy of the magnetic field, a frame rate affected by the number of receivers (LaScalza et al 2003 ), any restricted movement from tethered cable connections causing a hindrance to subjects (Sorriento et al 2020 ), a sensitivity to metal and other electronics (Meyer et al 2008 ; Ng et al 2009 ), and a smaller number of body segments that can be tracked due to limited number of physical sensors (Murphy et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%